The Effectiveness of Describing Picture Through Roundtable Technique in Teaching Speaking - Nadea Khotrun Nada; Olyvia Revalita Candraloka (Departement of Mathematics Education, 2024)
The objective of this research is to determine the effectiveness describing picture through roundtable technique in improving students speaking skills. This research used quantitative method. This research was conducted on tenth grade students of SMAN 1 Tahunan academic year 2023/2024. This study employed a true-experimental with pre-test and post-test design. The population of this research was tenth grade students of SMAN 1 Tahunan. The sample of this research was 2 classes, experimental class (X-11) and control class (X-12). To collect data, the researcher conducted an oral test to assess the students’ speaking skill.The result of this study is the experimental class had a mean score was 79,78 and the control class was 59,72. Then, the T-test analysis revealed that Sig. (2-tailed) was 0,000 which less than 0,05 and the T-test was more than T-table (11,946 > 1.690). The result of this research that using describing pictures through roundtable technique was effective in improving students’ speaking skill. The impact of this research can provide many media or methods in speaking teaching classes. So that students become more active and interested in the learning process.